Potential Biotechnological Applications of Autophagy for Agriculture - Thanthrige, Nipuni; Bhowmik, Sudipta Das; Ferguson, Brett J.; Kabbage, Mehdi; Mundree, Sagadevan G.; Williams, Brett (Frontiers in Plant Science, 2021)
Autophagy is a genetically regulated, eukaryotic cellular degradation system that sequestrates cytoplasmic materials in specialised vesicles, termed autophagosomes, for delivery and breakdown in the lysosome or vacuole. In plants, autophagy plays essential roles in development (e.g. senescence) and responses to abiotic (e.g. nutrient starvation, drought and oxidative stress) and biotic stresses (e.g. hypersensitive response). Initially, autophagy was considered a non-selective bulk degradation mechanism that provides energy and building blocks for homeostatic balance during stress. Recent studies, however, reveal that autophagy may be more subtle and selectively target proteins, protein complexes and even organelles for degradation to regulate vital cellular processes even during favourable conditions. The selective nature of autophagy lends itself to potential manipulation and exploitation as part of designer protein turnover machinery for the development of stress-tolerant and disease-resistant crops; crops with increased yield potential and agricultural efficiency; and reduced post-harvest losses. Here we discuss our current understanding of autophagy and speculate its potential manipulation for improved agricultural performance.